2012
DOI: 10.1177/147323001204000411
|View full text |Cite
|
Sign up to set email alerts
|

Altered Aggrecan Synthesis and Collagen Expression Profiles in Chondrocytes from Patients with Kashin—Beck Disease and Osteoarthritis

Abstract: Biochemical and morphological mechanisms underlying Kashin-Beck disease and OA include enhanced dedifferentiation and hypertrophy of chondrocytes, increased type I, III and X collagen levels, and suppressed type II collagen and aggrecan production compared with control samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Previous studies have observed that dysfunction of type II collagen contributed to the cartilage lesion of KBD patients. For instance, the expression level of type II collagen in KBD articular cartilage was significantly lower than that in healthy articular cartilage2425. Serum type II collagen can serve as the biomarker of the joint damage of KBD26.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have observed that dysfunction of type II collagen contributed to the cartilage lesion of KBD patients. For instance, the expression level of type II collagen in KBD articular cartilage was significantly lower than that in healthy articular cartilage2425. Serum type II collagen can serve as the biomarker of the joint damage of KBD26.…”
Section: Discussionmentioning
confidence: 92%
“…Articular cartilage ECM consists of a complex mixture of PGs, collagens, aggrecan, and serves an important role in the maintenance of tissue morphogenesis and function 19 . Former studies observed decreased content of PGs and aggrecan in the deep zone of KBD cartilage [20][21][22][23] . In this study, the protein-protein interaction and KEGG pathways analyses indicated that collagens (COL1A1, COL1A2, and COL4A1), were relatively decreased www.nature.com/scientificreports www.nature.com/scientificreports/ in the KBD group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with brachymorphic mice, nanomelic chick, dyschondroplastic chicken and Cmd mutant mice clearly show the importance of aggrecan in growth plate cartilage development and skeletogenesis. Furthermore, individuals suffering from Kashin–Beck disease, an endemic osteochondropathy that occurs in certain parts of China, is characterised by small stature and deformities of the limbs and digits, distorted growth plates, chondrocyte apoptosis and low levels of aggrecan [ 37 , 38 , 39 , 40 , 41 ]. The correct sulphation of the CS chains of aggrecan is essential to generate functional determinants capable of interacting with growth factors and morphogens [ 42 , 43 , 44 , 45 ].…”
Section: Cs Sulphation On Aggrecan Is An Important Functional Detementioning
confidence: 99%